Structural setting and metamorphic evolution of a contact aureole: the example of the Mt.Capanne Pluton (Elba Island, Tuscany, Italy) - Pandeli, Enrico; Giusti, Riccardo; Elter, Franco Marco; Orlando, Andrea; Orti, Letizia (Ofioliti, 2018)
This paper shows an updated geological, petrographical-chemical and structural picture of the contact aureole of the 6.9 Ma Mt. Capanne monzogranitic pluton in western Elba Island (Tuscan Archipelago), that is one of the most known Tertiary intrusive bodies in Italy. Most of the foliated metamorphic rocks derived from a Mesozoic Ligurian-type ophiolitic succession (Punta Polveraia-Fetovaia Unit) and are in the horneblende to pyroxene hornfels facies with estimated Tpeak > 610°C (locally > 650°C). Local variations of the metamorphic zonation of the at least 150-200 m thick aureole are due to the different lithological, physical and structural (e.g., bedding, fracturing) nature of the original rocks, but also to hydrofracturing phenomena which occurred during the syn-metamorphic upflow of the metasomatic hot fluids. The history of the emplacement and uplift of the Mt. Capanne pluton was defined through the metamorphic-structural evolution of its contact metamorphic aureole. The growth of the thermometamorphic minerals took place in several stages being both syn-kinematic with respect to the main ductile D2 folding event (connected to the plutonic intrusion) and static post-kinematic one. Ductile shear zones, characterized also by mylonites, were also active during recrystallization in a general shear-type regime (average value of Wm = 0.7) related to the vertical uplift of the pluton (pure shear) and lateral ductile flow of the covers (simple shear). The exhumation of the cooled pluton continued producing tangential cascade-type folding event (D3), detachment faults, and later high-angle faulting in the host rocks. The role of Western Elba in the geological frame of the whole island since Late Miocene times is also outlined in the paper.